Analysis of surgical treatment of tibial fractures fractures during the antiterrorist operation - Korol, Sergii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
Objective: To analyze the surgical procedures performed at all levels of medical care in the wounded with gunshot fractures of the tibia and severed limbs during the anti-terrorist operation (ATO). Methods:it is analyzed medical care in 118 wounded (May 2014–April 2015) with tibial gunshot fractures in 111 (94.07 %) and severed limbs — 7 (5.93 %). Results: in the wounded with tibial gunshot fractures and severed limbs temporary bleeding control, aseptic bandage application, pain management transport immobilization with improvised means provided at the primary and I medical care levels with following evacuation to the II level of the medical care. Beginning from the II level, all wounded underwent primary surgical treatment (PST). Osteosynthesis with external fixation device (EFD) performed in 76.27 % patients, revision surgical treatment (ST) — in 72.03 %, fasciotomy — in 23.73 %, free autodermoplasty — in 15.25 %, Ilizarov device osteosynthesis — in 15.25 %, amputation — in 10.17 %, nailing — in 8.47 %, plating — in 5.93 %, autogenous prosthesisng — in 5.08 %, VAC therapy — in 4.24 %, revision surgical treatment — 3.38 %. At the II level of medical care PST, final bleeding control, fasciotomy and stable fixation with external fixation device performed mainly. At the III and IV levels revision ST with VAC-therapy and ultrasound cavitation executed. After the soft tissue healing with the inflammation signs absence in 14.40 % patients external fixation device changed to the plate or nail. After 6–12 month good functional results obtained in 54.31 % of patients, satisfactory — in 30,17 %, unsatisfactory — in 15.52 %. Organizational, treatment and diagnostic mistakes were analyzed.